2008
DOI: 10.1111/j.1471-0528.2008.01737.x
|View full text |Cite
|
Sign up to set email alerts
|

Folic acid use in pregnancy and embryo selection

Abstract: Objective  Folic acid supplement use is recommended in pregnancy to reduce the risk of neural tube defect but concerns have been raised that increasing folic acid intake may select for embryos with genotypes that increase disease risk in the offspring. Our aim was to test for this effect. Design  Observational prospective cohort study. Setting  Aberdeen Maternity Hospital. Population or Sample  Women born before the introduction of folic acid advice (1970–80) and carrying singleton pregnancies (n = 1234) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…This result cannot be considered as a risk factor because the analysis of the 1298AA and 1298CC genotype frequencies showed similar distribution in children with NTDs and their mothers compared to controls. Similarly, Haggarty et al (2008) reported that the frequency of the 1299CC genotype was essentially the same in the children and their mothers (9.0 and 9.1%, respectively). Furthermore, Cunha et al (2002) could not find a direct association between the A1298C polymorphism and occurrence of NTDs.…”
Section: Discussionmentioning
confidence: 79%
“…This result cannot be considered as a risk factor because the analysis of the 1298AA and 1298CC genotype frequencies showed similar distribution in children with NTDs and their mothers compared to controls. Similarly, Haggarty et al (2008) reported that the frequency of the 1299CC genotype was essentially the same in the children and their mothers (9.0 and 9.1%, respectively). Furthermore, Cunha et al (2002) could not find a direct association between the A1298C polymorphism and occurrence of NTDs.…”
Section: Discussionmentioning
confidence: 79%
“…Furthermore, the selective significance of the T allele was supported by the results of the analysis of the distribution of the frequencies of alleles, genotypes, and haplotypes of the С677Т and А1298С polymorphisms in the MTHFR gene in the Israeli, Japanese, and African populations. According to these data, the 677T allele is found in the haplotypes with a selective advantage [69]. …”
Section: Resultsmentioning
confidence: 99%
“…Haggarty et al report that folic acid intervention has not resulted in genetic selection in favour of the MTHFR 677T allele [27], however this does not take into account potential gene-gene interactions at other folate-related loci and does not discount the possibility that numerous genetic variants may act in concert to exert selective pressure.…”
Section: Discussionmentioning
confidence: 99%